(untitled) (Forum Agribisnis, 2020)
Community-scale biogas digester would become an alternative that reduces the cost of constructing biogas facilities. However, it is important to identify ideal locations of digesters to optimize distribution process of biogas input materials to digester facilities. This research aims to determine optimal locations of digester using geospatial kernel density analysis by calculating the biogas raw material using the total mass of the solid waste, which is applied on cowshed locations of Sumber Rejeki Dairy Cooperation in Pudak Wetan, Ponorogo. The results of the analysis have found nine ideal locations which community scale biogas digester facilities can be built by considering the density of the total mass of the solid waste and the proximity of the cowsheds on the research location.